2011
DOI: 10.4103/0250-474x.99017
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a UV spectrophotometric method for the simultaneous estimation of eprosartan mesylate and hydrochlorothiazide in bulk and formulations

Abstract: A simple, efficient, precise and accurate absorbance ratio method have been developed for the estimation of eprosartan mesylate and hydrochlorothiazide in pure and in fixed dose combination. In this method, UV spectra of eprosartan mesylate and hydrochlorothiazide were overlayed which involves the formation of Q-absorbance equation at 249.1 nm (isobestic point) and 274.5 nm, the max of hydrochlorothiazide. Both the drugs obeyed Beers law in the concentration range of 6-36 μg/ml and 1-10 μg/ml for eprosartan me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The recoveries of EM, EMP RC01 and EMP RC05 were evaluated. The mean percentage recoveries for LOQ, 50%, 80%, 100%, 150% and 200% accuracy were found to be 101.5%±1 5,. 107%±1.6, 104.6%±0.4, 102.8%±0.4, 101.7%±0.3 and 101.3%±0.2 respectively for EM; 103.9%±1.2, 96%±1.4, 96.2%±0.7, 97.5%±0.2, 98.1%±0.3 and 97.8%±0.2 respectively for the EMP RC01; and 98.6%±1.1, 103%±2.9, 99%±2.0, 96.8%±0.8, 96.2%±1.3 and 101.7%±0.6 respectively for the EMP RC05.…”
mentioning
confidence: 91%
See 2 more Smart Citations
“…The recoveries of EM, EMP RC01 and EMP RC05 were evaluated. The mean percentage recoveries for LOQ, 50%, 80%, 100%, 150% and 200% accuracy were found to be 101.5%±1 5,. 107%±1.6, 104.6%±0.4, 102.8%±0.4, 101.7%±0.3 and 101.3%±0.2 respectively for EM; 103.9%±1.2, 96%±1.4, 96.2%±0.7, 97.5%±0.2, 98.1%±0.3 and 97.8%±0.2 respectively for the EMP RC01; and 98.6%±1.1, 103%±2.9, 99%±2.0, 96.8%±0.8, 96.2%±1.3 and 101.7%±0.6 respectively for the EMP RC05.…”
mentioning
confidence: 91%
“…The principal objective for that is to enhance the conditions and parameters, which should be observed in the evolution and establishment. From the literature review, it was found that there are few methods for the estimation of EM, Impurity A and Impurity B. but many methods for individual analysis of the drugs are present [5][6][7][8][9][10][11][12][13][14]. Hence it is aimed to acquire novel methods for the estimation of EM, impurity A and Impurity B using available analytical technique HPLC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, as per ICH guideline Q3A (R2), analytical monitoring of impurities in drug substances and formulations is very crucial for quality assurance and safety of the drug . An extensive literature search revealed that a few analytical methods have been reported for the determination of EPR alone and in combination with other drugs in bulk and different formulations by using UV spectrophotometry and LC techniques. A stability‐indicating UHPLC method was reported for simultaneous determination of EPR and hydrochlorothiazide.…”
Section: Introductionmentioning
confidence: 99%